Interim regret minimization - HE, Wei (Institutional Knowledge at Singapore Management University, 2024)
We consider a robust version of monopoly pricing when the seller only knows the bound on valuations and the mean of the distribution of the buyer’s value. The seller seeks to minimize interim regret, the forgone expected revenue due to not knowing the distribution of the buyer’s value. The optimal pricing policy randomizes over a range of prices; the support of the pricing policy is bounded away from zero.